Changes of dumps coal washing microbiocenosis in the process of accumulation - Блайда, И. А.; Васильева, Т. В.; Баранов, В. И.; Слюсаренко, Л. И.; Шулякова, С. Н. (Problems of Environmental Biotechnology, 2016)
Technogenic waste of coal benefication on the central concentrator "Chervonogradska" regardless of storage time have a complicated mineralogical composition and contain high concentrations of heavy metals, which makes them an ecological hazardous. The bacterial leaching methods of this kind of raw material for its recycling are cost-effective, resource-saving and environmentally friendly. To use them effectively is necessary know the composition and oxidative activity of own microbial associations of technogenic waste. The concentration of the valued components in the waste dumps of different shelf life were determined by standard physico-chemical methods. The influence of its own microbiota on extracting metals from waste dumps has been shown. The structure and quantitative composition of the enrichment cultures of microorganisms that has been isolated from dumps with different shelf life have been described. It has been shown that the qualitative composition not independent of storage time but the number of microorganisms is several times higher in dumps of long storage. It was found that the dominant part of microbiocenoses are acidophilus chemolithotrophic bacteria – mesophilic and moderately thermophilic bacteria of the genera Acidithiobacillus and Sulfobacillus. The maximum leaching effect was achieved by using as an energy source of divalent iron as in mesophilic and in moderately thermophilic conditions. The maximum extraction of valuable metals in the solution were obtained after processing a technogenic waste with a small storage term regardless from used group of microorganisms.